ANALISIS PENGARUH SERVICE QUALITY DAN CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION PADA BANK SYARIAH KABUPATEN KOLAKA SULAWESI TENGGARA - Endang Puspita; Munadi Idris; Muhammad Akbar (Jurnal Ekonomi Bisnis Syariah, 2020)
There are two Sharia Banks in Kolaka Regency, namely BNI Syariah Bank KCP Kolaka and Bank Muamalat Indonesia Tbk KCP Kolaka. The determinants of customer satisfaction include service quality and customer experience. To attract the hearts of its customers, every company, especially the Kolaka Regency Sharia Bank, must always provide and pay attention to customer satisfaction. The formulation of the problem in this study is whether there is a simultaneous influence of Service Quality and Customer Experience on Customer Satisfaction at the Kolaka Regency Sharia Bank? The purpose of the study was to determine whether there was a simultaneous influence of Service Quality and Customer Experience on Customer Satisfaction at the Kolaka Regency Sharia Bank. The research method used in this study is to use a quantitative approach. Determination of the number of representative samples that depends on the number of indicators multiplied by 5 based on the results of a questionnaire with a total of 65 respondents. The sampling technique used is the Accidental Sampling method, which is a sampling technique based on chance. The data sources used are primary and secondary data sources, the data in this study are direct answers assisted by questionnaires or questionnaires given directly by customers to be filled in according to the actual situation. Data analysis techniques through the SPSS 0.20 program are Validity, Reliability, Classical Assumptions Test, and Statistics. The results showed that by using a questionnaire or questionnaire, researchers obtained research results by showing that partially the Service Quality Variable (X1) had no positive and significant effect on the Customer Satisfaction Variable (Y) with a Sig value. Of 0.154 while the Customer Experience Variable (X2) has a positive and significant effect on the Customer Satisfaction Variable (Y) with a Sig value of 0.000. Meanwhile, the Service Quality and Customer Experience variables simultaneously have a positive and significant influence on the Customer Satisfaction Variable.